The Organizational-Economic Mechanism for Enhancing Technoparks’ Participation in Innovation Development in China and Belarus - Wang, Jiahe (International Journal of Multidisciplinary Research, 2026)
The issue of cooperation between the Republic of Belarus and China in the field of innovation is currently becoming increasingly relevant. The study examines the factors and conditions for effective operation of technology parks in China and Belarus, considering state regulation, focus on developing external markets, lobbying for budgetary spending on R&D, implementing preferential policies, and maintaining genuine communication with leading universities. This article explores the potential for collaboration between the Republic of Belarus and the People’s Republic of China in establishing industrial parks, drawing on successful international technology park models such as the "Great Stone" and "Silk Road" initiatives.